Macroeconomic Determinants of the Indonesian Composite Stock Price Index: An ARDL Approach (2016-2025) - Siti Syefira Salsabila; Al’an Falina Rizkya; Rizke Maulina; Nuresti Supartini; Gusganda Suria Manda (Manunggal Halim Jaya, 2027)
This study investigates the short and long run impacts of macroeconomic variables inflation, the BI Rate, the USD/IDR exchange rate, and world gold prices on the Indonesian Composite Stock Price Index (IHSG). Utilizing 120 monthly observations from January 2016 to December 2025, this period accounts for severe market turbulences, including the early 2025 trading halts. Given the mixed integration orders I(0) and I(1)), an ARDL bounds testing framework and an Unrestricted Error Correction Model (UECM) with HC3 robust standard errors were applied. The ARDL bounds test reveals no stable long run cointegration (F